Eyes in the wild: Thelazia callipaeda in wild carnivores of Croatia - Ema Gagović; Šimun Naletilić; Daria Jurković Žilić; Željko Mihaljević; Adnan Hodžić; Relja Beck (Parasites & Vectors)
Abstract Background Thelazia callipaeda is an emerging zoonotic nematode that infects the eyes of domestic and wild mammals across Europe and is transmitted by drosophilid flies of the genus Phortica. Despite increasing reports across the continent, its distribution in wildlife in southeastern Europe remains poorly understood. To our knowledge, this study represents the first comprehensive parasitological and molecular investigation of T. callipaeda in wild carnivores in Croatia. Methods Between 2020 and 2023, a total of 2632 animals, either legally hunted or found dead, were examined. These included 1794 red foxes (Vulpes vulpes), 443 golden jackals (Canis aureus), 180 European badgers (Meles meles), and 215 stone martens (Martes foina). Ocular examination and nematode collection were conducted, followed by morphological identification and COI gene sequencing for species confirmation. Results The overall prevalence of T. callipaeda infection was 3.9% in red foxes and 4.3% in golden jackals. No infections were detected in badgers or martens. The infections were geographically restricted to continental regions, with the highest prevalence recorded in eastern counties. Seasonal patterns were evident in red foxes, where infection rates and reproductive activity peaked in autumn and winter. In contrast, golden jackals showed more stable infection rates throughout the year. A significant proportion of infections involved gravid females, particularly in jackals (73.7%), suggesting their critical role in sustaining transmission cycles. Molecular analysis confirmed that all isolates belonged to T. callipaeda haplotype 1. Conclusions These findings highlight the established presence of T. callipaeda in Croatian wildlife and reveal distinct host-specific patterns in prevalence, seasonality, and reproductive dynamics. Red foxes may act as seasonal reservoirs of infection, while golden jackals could serve as year-round reservoirs. Considering the zoonotic potential of this parasite, further surveillance and integrated monitoring of vectors and vertebrate hosts are essential for evaluating future risks to public and veterinary health in the region. Graphical abstract